Nanostructured Black Phosphorus/Ketjenblack–Multiwalled Carbon Nanotubes Composite as High Performance Anode Material for Sodium-Ion Batteries - Xu, Gui-Liang; Chen, Zonghai; Zhong, Gui-Ming; Liu, Yuzi; Yang, Yong; Ma, Tianyuan; Ren, Yang; Zuo, Xiaobing; Wu, Xue-Hang; Zhang, Xiaoyi; Amine, Khalil (Nano letters, 2016)
Sodium-ion batteries are promising alternatives to lithium-ion batteries for large-scale applications. However, the low capacity and poor rate capability of existing anodes for sodium-ion batteries are bottlenecks for future developments. Here, we report a high performance nanostructured anode material for sodium-ion batteries that is fabricated by high energy ball milling to form black phosphorus/Ketjenblack–multiwalled carbon nanotubes (BPC) composite. With this strategy, the BPC composite with a high phosphorus content (70 wt %) could deliver a very high initial Coulombic efficiency (>90%) and high specific capacity with excellent cyclability at high rate of charge/discharge (∼1700 mAh g–1 after 100 cycles at 1.3 A g–1 based on the mass of P). In situ electrochemical impedance spectroscopy, synchrotron high energy X-ray diffraction, ex situ small/wide-angle X-ray scattering, high resolution transmission electronic microscopy, and nuclear magnetic resonance were further used to unravel its superior sodium storage performance. The scientific findings gained in this work are expected to serve as a guide for future design on high performance anode material for sodium-ion batteries.